Directed – Project Based Learning (DPjBL) as a language learning model to improve students’ english achievement - Tri Pratiwi; Sufyarma Marsidin; Hermawati Syarif; Yahya Yahya (Fakultas Ilmu Pendidikan UNP)
This research aimed to improve students’ English achievement by developing learning model in English subject for VIII graders of SMP N 1 Uram Jaya through Directed-Project Based Learning (DPjBL) implementation. This study is designed in Research and Development (R & D) using ADDIE model development. Test instrument for finding out the effectiveness of DPjBL and also students English achievement which were then analyzed quantitatively by using T-test. The results showed that DPjBL is effective to use, it is seen from the difference in value between the pretest and post-test of the control class and the experimental class. From the results of a questionnaire filled in general, the students and teachers agreed to DPjBL learning model. The practicality of teacher book got 93. 3 and the practicality of students book got 97.0. It shows that DPjBL is an effective learning model and this learning model can increase the students' English achievement.